Analysis of Voice Recognition System on Translator for Daily Use - Yudi Aryatama Fonggi; Tio Oktavianus (Bina Nusantara University, 2021)
This research paper’s aim is to analyse the usage and the implementation of voice recognition system in translator device by reviewing some of literatures in aspect of linguistic and voice recognition system. This research purpose is to understand the procedure of how the voice recognition system is implemented and what the impact of using the translator device for daily use is in a lot of field. This paper also include a review about what is the importance of multilinguistic skill, what is the problem that we usually have in multilinguistic communication usually in global environment, How the basic system that usually use in voice recognition system so the reader can learn by describing the procedure of voice recognition system,In what way the implementation of voice recognition in translator device by providing some example of the devices, and How is the development of the translation devices and the example of translator device usage in society.